Analysis of Half-Value Layer on Multimeters and Manual Calculation Using Aluminum Filter - Alwali Walyatalattov Solichin; Freddy Haryanto (Journal of Medical Physics and Biophysics, 2023)
Limited number of qualified test laboratories leads to a long queue of calibration and conformity tests. X-Ray beam quality test that utilizes the half-value layer method might be used as an option for the internal test procedures to optimize the radiation protection program by the medical physicist. RADCAL and RAYSAFE were used as the multimeters for this experiment, with the exposure setting of 53 kV, 160 mA, and 50 ms. The best result is produced by the configuration where the Al plate is placed close to the source, right below the collimator, with a 2,5% mean deviation from the multimeter’s HVL value. Meanwhile, when the Al plate is placed close to the multimeter sensor, the mean deviation can reach up to 13,5%. It can be concluded that the HVL method using an Al plate and detector can be used to measure the beam quality of the radiographic X-Ray machine. This research has no intention to replace the existing procedure but to add more insight for medical physicists’ QA/QC program. As radiation safety and protection must also be considered, not only for certifications but also actualizations.